BUYING BEHAVIOUR PATTERN ON ONLINE CONSUMER - mahjudin, mahjudin (Economic and Bussiness Faculty, Dr Soetomo University, 2019)
ABSTRACT Since the beginning of the Internet, individiuals have shown interest to the Internet. According to Internet World Stats' statistics (2012) today more than two billion people linked to the Internet. This number shows that 30 percent of the world population use the Internet. Consequently, the Internet can be used for the competitive advantage by organisations and actually it is a powerful source to use (Hamill, 1997; 300).Customer behaviours are influenced by different factors such as culture, social class, references group relation, family, salary level and salary independency, age, gender etc. and so they show different customer behaviours. These differences are seen more specific when it is considered between two different consumer groups from different countriesThis paper using online questioner, since the research was an online consumer behaviour study, online data collection methods were preferred. The link of the questionnaire has been sent online. 184 were responded and within the responded questionnaires 169 were usable for analysis (six incomplete responses have been eliminated). The sample consisted of individuals that live urban area which is Jakarta and Surabaya and rural cities which is Klaten and Madiun.The result of this study would contribute marketers who want to penetrate the market in 4 cities who is already present in the market and wants to maintain the loyalty of their customers. It can also be a part of the study on international consumer behaviour toward online shopping.